Cavernous Sinus Involvement and Near Miss Mediastinitis following Mandibular Tooth Infection Treated during the COVID-19 Pandemic: Clinical Diagnosis and Treatment - Alessio Danilo Inchingolo; Sabino Ceci; Luisa Limongelli; Alberto Corriero; Luigi Curatoli; Daniela Azzollini; Pietro Paolo Mezzapesa; Grazia Marinelli; Giuseppina Malcangi; Giovanni Coloccia; Mario Ribezzi; Maria Massaro; et al. (Case Reports in Dentistry)
Odontogenic infections represent a frequent condition that in some cases, if not treated promptly, can spread quickly to the rest of the body and turn into life-threatening infections. In this work, the case is reported of a 59-year-old woman, diabetic and overweight, who presented to the Odontostomatology and Otolaryngology Section of the Policlinic of Bari with mandibular tooth infection that had developed into a deep neck space infection leading to the involvement of cavernous sinuses and near mediastinum. The diagnosis, the surgical drainage of the phlegmon and removal of infection foci, appropriate control of the airways, and a correct antibiotic therapy made it possible to avoid a potentially fatal condition. Prompt management and early diagnosis of deep space neck infections, such as phlegmon and/or necrotizing fasciitis, with the auxilium of CT scans and tools such as LRINEC (Laboratory Risk Indicator for Necrotizing Fasciitis), NLR (Neutrophil-to-Lymphocyte Ratio), and LRINECxNLR scores (Laboratory Risk Indicator for Necrotizing Fasciitis and Neutrophil to Lymphocyte Ratio), are advised to evade delays and complications that could potentially worsen the patient’s outcome.